Which Piotr Skarga’s Edition of Żywoty Świętych Was Used for Translation into Old Church Slavonic: The Life of St. Procopius of Scythopolis - Sapozhnikova, Galina (Slavistica Vilnensis, 2021)
The article deals with a small private episode of the general topic of research into Cyrillic translations of an extensive Polish book Żywoty Świętych by Piotr Skarga, a Jesuit and the first rector of the Vilnius University. Using as an example the Old Church Slavonic life of St. Procopius of Scythopolis, translated from Skarga’s book and contained in two manuscripts originating from the territories of the Kingdom of Poland, the author shows that a comparison of the Church Slavonic translation with its Polish original, taking into account all textual changes made in the lifetime editions of Żywoty Świętych makes it possible to determine the exact edition used as a source for the Old Church Slavonic the translation. At the same time, this will serve as a chronological marker indicating the time before which the translation could not have appeared
Keywords: Grand Duchy of Lithuania; Kingdom of Poland; Piotr Skarga; translated hagiography; Old Church Slavonic translations from Polish